ANALISA YURIDIS TENTANG STATUS KEWARGANEGARAAN ANAK HASIL PERKAWINAN CAMPURAN MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN INDONESIA - Purnamawati, Evi (Faculty of Law, University of Palembang, 2019)
The citizenship status of a child born of a mixed marriage under Law No. 12 of 2006 on Indonesian Citizenship is a positive enlightenment, since the Act allows for limited dual citizenship for a child of mixed marriage, up to the age of 18 years, the child is entitled to choose citizenship which he wanted and given time to think for 3 years. Whereas in Law Number 62 Year 1958 on Citizenship, the Status of the nationality of a child follows the citizenship of his father. Limitation on the rights and obligations of a child born of a mixed marriage under Law Number 12 of 2006 on Indonesian Citizenship is to have the same rights and obligations that a person of a citizen with a dual citizenship status is legally recognized as being citizen in both countries: Indonesian Citizen and Foreigners. Since he is a resident of both countries, the inherent rights due to his citizenship must also be fully provided by the state and the state shall not limit his rights as a citizen of both countries.